Limites morfoestruturais do Chaco no Brasil - JÉSSICA LIMA VIANA (2024)
The Chaco has a great wealth of biodiversity that has long suffered from the neglect of specific public policies and the fragmentation of its habitat due to human actions. This biome has domains in Argentina, Bolivia, Paraguay and Brazil, although in the latter it is not officially recognized as a biome. Understanding the structural control of the landscape is of fundamental importance, as it directly influences all forms of life, affecting ecosystems, fauna and flora in a given region. This work aims to understand whether there is a control system equivalent to that observed in the Pantanal, in the Brazilian Chaco. Therefore, data from the Radar Topography Mission (SRTM) and images from the United States Geological Survey (USGS) Landsat 8-9 OLI/TIRS satellite will be used, as well as free software such as System for Automated Geoscientific Analyzes (SAGA) (Farr, et al., 2007), WhiteBox (Lindsay, 2016) and QGIS (QGIS Development Team, 2023). A systematic literature review and bibliometric analysis of publications from January 1993 to March 2023 with the string “Chaco” were carried out. The search resulted in 18 articles that made up the final analysis. The keyword network showed that Argentina is the country that produces the most work on the Chaco and has the highest correlation with other groups such as South America. The co-authorship network revealed that Rossello, E. A. is a key author within the analyzed portfolio, linked to the main authors from other research groups. Finally, from the research questions it was possible to observe that there is no geographical definition in the literature of the Chaco biome in Brazil, in most contexts it appears as a sub-region of the Pantanal. Likewise, there is no geographical delimitation of structural blocks in the Chaco of Brazil. The specific characteristics of the Chaco, on Brazilian soil, have also not been identified. These results highlight the gaps and opportunities for Chaco research in Brazil and reveal the unprecedented contribution of this work.